Evaluation of Fruit Sorbets Consumer Preferences - Palka, A.; Karczmarczyk, P. (Scientific Journal of Gdynia Maritime University, 2018)
Surveys were conducted on consumer preferences in relation to fruit sorbets. 120 people were subject to the survey and the questionnaire was carried out online. Based on the conducted tests, it was found that sorbet is relatively rarely consumed by the respondents, and strawberry sorbet could be their favourite taste. Among the examined brands, the Grycan brand was the most popular.